2021
DOI: 10.1186/s43088-021-00124-9
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-communicative interruptions in hearing-impaired Egyptian Arabic-speaking children

Abstract: Background Hearing is critical for normal development and acquisition of language and speech, and hearing impairment exists when there is diminished sensitivity to the sounds normally heard. Several studies have suggested that one out of every two to three school-aged children with any degree of hearing impairment have academic, social, and behavioral difficulties. Purpose: to compare the degree of hearing loss regarding the psychological profile: behavioral, social, emotional, and cognition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The concept of Oral Health-related Quality of Life (OHRQoL) assesses the functional, social, and psychological effects of oral diseases [ 9 ], revealing significant differences between healthy children and those with general diseases [ 10 ]. Mild to moderate hearing impairment can lead to negative consequences affecting psychological, behavioral, social, and emotional development [ 11 ], impacting oral hygiene practices and quality of life [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of Oral Health-related Quality of Life (OHRQoL) assesses the functional, social, and psychological effects of oral diseases [ 9 ], revealing significant differences between healthy children and those with general diseases [ 10 ]. Mild to moderate hearing impairment can lead to negative consequences affecting psychological, behavioral, social, and emotional development [ 11 ], impacting oral hygiene practices and quality of life [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted comparison research to demonstrate the effectiveness and robustness of suggested method vs established approaches based on k-nearest neighbors (KNN) and Support Vector Machines (SVM). Hearing is essential for normal language and speech development, and hearing impairment occurs whenever the acuity to normally heard noises is reduced [11]. Many studies show that one out of once each three to four educated citizens with any degree of hearing loss faces educational, social, and impede learning.…”
Section: Literature Reviewmentioning
confidence: 99%